Assessing the Association Between Nutritional Status, Caries, and Gingivitis in Schoolchildren: A Cross-Sectional Study - Mariane C.F. Barbosa MS; Caio L.B. Reis DDS; Célia M.C.F. Lopes PhD; Isabela R. Madalena PhD; Erika C. Küchler PhD; Flares Baratto-Filho PhD; Carmen L.M. Storrer PhD; Daniela C. Lima PhD; Daniela S.B. Oliveira PhD (SAGE Publishing, 2021)
Objective. To evaluate if nutritional status is associated with caries and gingivitis in Brazilian schoolchildren. Material and methods. Children of both genders, age ranging from 8 to 11 years old, were included in this study. Caries was diagnosed using ICDAS (International System for Detection and Assessment of Carious Lesions) and gingivitis was diagnosed using the Community Periodontal Index. The nutritional status of each child was defined by BMI Z-score calculation. Data on oral health behavior and dietary habit were collected through parent's questionnaires. Parametric analyzes were performed to compare the groups. The established alpha was 5%. Results. The sample consisted of 353 schoolchildren: 16 underweight children, 247 eutrophic children, 64 overweight children, and 26 were obese children. Overweight, Obese and Overweight + Obese children presented less cavitated caries lesion than Eutrophic children ( P < .05). Gingivitis was not associated with nutritional status ( P > .05). Conclusion. Caries was associated with overweight and obesity in Brazilian schoolchildren.